2015
DOI: 10.1016/j.jaci.2015.05.044
|View full text |Cite
|
Sign up to set email alerts
|

The airway microbiome in patients with severe asthma: Associations with disease features and severity

Abstract: Background Asthma is heterogeneous, and airway dysbiosis is associated with clinical features in mild-moderate asthma. Whether similar relationships exist among patients with severe asthma is unknown. Objective To evaluate relationships between the bronchial microbiome and features of severe asthma. Methods Bronchial brushings from 40 participants in the BOBCAT study (Bronchoscopic Exploratory Research Study of Biomarkers in Corticosteroid-refractory Asthma) were evaluated using 16S rRNA-based methods. Rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
408
4
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 429 publications
(454 citation statements)
references
References 42 publications
19
408
4
4
Order By: Relevance
“…The healthy airways also exhibit niche specificity, in that specific sites such as the nares and the oropharynx exhibit distinct distributions of bacterial taxa, with the former enriched for skin-associated Actinobacteria and the latter enriched more commonly for members of the Firmicutes and Proteobacteria (21). In contrast to healthy subjects, patients with airway diseases such as asthma exhibit a significant increase in the burden of bacteria present in the lower airways; moreover, the composition of these lower-airway communities is related to features of the disease (20,22).…”
Section: Relationships To Diseases Of the Lungs And Airwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The healthy airways also exhibit niche specificity, in that specific sites such as the nares and the oropharynx exhibit distinct distributions of bacterial taxa, with the former enriched for skin-associated Actinobacteria and the latter enriched more commonly for members of the Firmicutes and Proteobacteria (21). In contrast to healthy subjects, patients with airway diseases such as asthma exhibit a significant increase in the burden of bacteria present in the lower airways; moreover, the composition of these lower-airway communities is related to features of the disease (20,22).…”
Section: Relationships To Diseases Of the Lungs And Airwaysmentioning
confidence: 99%
“…An independent study of induced sputum from 56 adults, including 26 individuals with severe asthma, indicated that enrichment of specific Streptococcus taxa is associated with recentonset asthma, rhinosinusitis, and sputum eosinophilia (23). Independently, Huang and colleagues demonstrated that the bronchial bacterial community composition in those with severe asthma (n = 40) was related to body mass index, sputum total leukocytes, and bronchial biopsy eosinophil numbers, with each of these factors associated with distinct airway bacterial community compositions (22). More specifically, positive associations were observed between biopsy eosinophil numbers and two members of the Actinobacteria (Streptomyces and Propionicimonas) in this study (22).…”
Section: Relationships To Diseases Of the Lungs And Airwaysmentioning
confidence: 99%
“…16S sequencing is much broader and gives little or no information about subspecies and antibiotic sensitivities that are important to the clinicians. Most publications relate to disease in which host-microbe interaction is likely to play a role in disease pathogenesis and ongoing disease flare; these are mostly chronic conditions such as inflammatory bowel disease (IBD), 4,[16][17][18] asthma, [19][20][21] skin conditions, 22 and cancers. [23][24][25] The immunomodulatory effect of the microbiome seems likely to hold a key to understanding several diseases, and correlation of host gene expression (transcriptome) with the microbiome and microbial gene expression may yield useful insights.…”
Section: Which Diseases Types May Be Of Interest To Microbiome Researmentioning
confidence: 99%
“…In previous airway studies, α diversity results were contradictory, which may be attributed to nonuniformity of the sampling sites and techniques [15, 16, 17, 18]. The CR, AR, and AS samples had similar principle component analysis clustering and, in spite of the presence of overlap between the controls and the disease groups, the results denoted the presence of dysbiosis in urine EVs of the CR, AR, and AS.…”
Section: Discussionmentioning
confidence: 82%